1994
DOI: 10.1136/gut.35.11.1523
|View full text |Cite
|
Sign up to set email alerts
|

Secondary oesophageal peristalsis in patients with non-obstructive dysphagia.

Abstract: Secondary peristalsis was investigated in 30 patients with non-obstructive dysphagia and 20 age matched controls. Oesophageal motility was recorded at 3 cm intervals along the oesophageal body. Primary peristalsis was tested with 5 ml water swallows. Secondary peristalsis was stimulated with 10 ml boluses of air and water injected in the midoesophagus and by distensions (5 seconds duration) with a 3 cm balloon at the same level. Primary peristalsis was normal in 19 of the 20 control subjects and in nine of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 20 publications
3
49
0
2
Order By: Relevance
“…Impaired distension-induced esophageal contractility and deficient acid clearance have been described in pa tients with gastroesophageal reflux [18,19] and an abnor mal distension response pattern has been noted in pa tients with functional dysphagia [20,21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired distension-induced esophageal contractility and deficient acid clearance have been described in pa tients with gastroesophageal reflux [18,19] and an abnor mal distension response pattern has been noted in pa tients with functional dysphagia [20,21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary peristalsis can be reliably triggered by intraoesophageal air or water infusion [3]. Although ample data are available in published works about the manometric characteristics and reproducibility of initiation of secondary peristalsis in health and a variety of disease states [3][4][5][6][7], there is a paucity of data on the efficiency of oesophageal bolus transport and clearance by secondary peristalsis in health or in disease.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal motility abnormalities (eg, simultaneous contractions and ineffective peristalsis) and impaired visceral sensitivity to chemical or mechanical stimuli have been suggested as underlying mechanisms [3]. Abnormal secondary peristalsis in the presence of normal primary peristalsis has been demonstrated in nine subjects with functional dysphagia [9]. In another study, the authors suggested that patients with nonobstructive dysphagia (including those with functional dysphagia) are more likely to demonstrate reduced perception thresholds to esophageal balloon distention than normal controls [10].…”
Section: Functional Dysphagiamentioning
confidence: 99%